Evaluation of environmental quality of Itaguaré river, Bertioga-sp , using toxicity tests and microbiological bathing conditions indexes - Aline Viana de Morais; Eduardo dos Santos Bretas; Camilo Dias Seabra Pereira; Fernando Sanzi Cortez; Augusto Cesar; Aldo Ramos Santos (O Mundo da Saúde, 2011)
According to Resolutions CONAMA N. 274/2000and N. 357/2005, bathing conditions and toxicity must be evaluated in an aquatic receiving body to foresee and prevent adverse effects to human health and aquatic biota. The present work evaluated the quality of waters of Itaguaré River (Bertioga - São Paulo) in five different points which differ as regards the occupation of its edges. For doing this, we applied eco-toxicological tests, measured the concentration of thermotolerant coliformis and physical-chemical parameters. We did tests of acute toxicity following ABNT 12713 (2004) and chronic toxicity following ABNT 13373 (2005) using cladocera as test-organisms, in addition to measuring thermotolerant coliformis through the technique of multiple pipes (APHA 2005), for detecting and quantificating fecal pollution by homeothermic animals. Results showed acute toxicity in Itaguaré River only in the autumn in points 1, 2 and 3, whereas chronic toxicity was observed in all seasons in points 1 and 2; and, in all the points (1, 2, 3, 4 and 5) in the spring and autumn. The levels of thermotolerant coliformis had low concentrations classified, as regards bathing conditions as excellent or very good cf. CONAMA N. 274/2000. However, there were greater concentrations of coliformis in points 1 and 2 during all months, and toxicity was also observed. These results suggest the presence of domestic effluent causing significant alterations in water quality in points 1 and 2, located next to Manoel Hypólito do Rego Highway.